Hubungan Usia Menarche dan Status Gizi Siswi SMP Kelas 2 Dengan Kejadian Dismenore - Dita Trimayasari; Kadar Kuswandi (Akademi Kebidanan La Tansa Mashiro, 2014)
The research objective was to determine the relationship of age and nutritional status menarhce second grader with dysmenorrhea events SMP Negeri 1 Warunggunung in February of 2013